HYBRID INFRASTRUCTURE PROJECT MANAGEMENT METHODOLOGIES - Denis Bushuiev; Boris Kozyr (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of this article is the development of hybrid methodologies for managing projects, programs and project portfolios. Significant reductions in the life cycles of infrastructure programs, which contain projects of different lines of activity and different management methodologies, for example, waterfalls with a rigid life cycle and Agile with a flexible methodology life cycle, require the use of convergence tools to form “hybrid” methodologies. The goal is to develop a convergent approach to building hybrid project management methodologies in terms of decision-making processes in project management based on various platforms. Results of the studies were obtained using a convergent approach to building methodologies for managing infrastructure projects and programs. A substantial model of the resulting hybrid methodology for managing infrastructure projects and programs is presented. Conclusions: Hybrid methodologies for managing infrastructure projects and programs are becoming more popular in this category of programs. The main reason is the presence in the program of components with different life cycles, and, consequently, methodologies that require integration and harmonization. The methodology is tested by the practice of using mechanisms of hybrid multilevel management of infrastructure projects and programs. The study of hybrid infrastructural program management methodologies is defined by the practice of introducing different components of programs. The application of the hybrid project management methodology allowed the authors to execute different projects in essence within the stipulated timeframe with the given budget and quality of construction projects and projects of creation of information and communication infrastructure management systems. Further areas of research are related to the elaboration of harmonization, integration, convergence and actualization mechanisms.